Transnasal Humidified Rapid Insufflation Ventilatory Exchange in children requiring emergent intubation (Kids THRIVE): a protocol for a randomised controlled trial. Issue 2 (20th February 2019) - George, Shane; Humphreys, Susan; Williams, Tara; Gelbart, Ben; Chavan, Arjun; Rasmussen, Katie; Ganeshalingham, Anusha; Erickson, Simon; Ganu, Subodh Suhas; Singhal, Nitesh; Foster, Kelly; Gannon, Brenda; et al.
Abstract : Introduction: Emergency intubation of children with abnormal respiratory or cardiac physiology is a high-risk procedure and associated with a high incidence of adverse events including hypoxemia. Successful emergency intubation is dependent on inter-related patient and operator factors. Preoxygenation has been used to maximise oxygen reserves in the patient and to prolong the safe apnoeic time during the intubation phase. Transnasal Humidified Rapid Insufflation Ventilatory Exchange (THRIVE) prolongs the safe apnoeic window for a safe intubation during elective intubation. We designed a clinical trial to test the hypothesis that THRIVE reduces the frequency of adverse and hypoxemic events during emergency intubation in children and to test the hypothesis that this treatment is cost-effective compared with standard care. Methods and analysis: The Kids THRIVE trial is a multicentre randomised controlled trial performed in participating emergency departments and paediatric intensive care units. 960 infants and children aged 0–16 years requiring emergency intubation for all reasons will be enrolled and allocated to THRIVE or control in a 1:1 allocation with stratification by site, age (<1, 1–7 and >7 years) and operator (junior and senior). Children allocated to THRIVE will receive weight appropriate transnasal flow rates with 100% oxygen, whereas children in the control arm will not receive any transnasal oxygen insufflation. The primary outcomes are defined as follows: (1) hypoxemic event during the intubation phase defined as SpO2 <90% (patient-dependent variable) and (2) first intubation attempt success without hypoxemia (operator-dependent variable). Analyses will be conducted on an intention-to-treat basis. Ethics and dissemination: Ethics approval for the protocol and consent process has been obtained (HREC/16/QRCH/81). The trial has been actively recruiting since May 2017. The study findings will be submitted for publication in a peer-reviewed journal. Trial registration number: ACTRN12617000147381.